2020
DOI: 10.1097/ogx.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Birth Plans and Unintended Maternal and Neonatal Consequences: A Review of the Literature

Abstract: Importance Birth plans are an important part of childbirth preparation for many women. Objective The aim of this review was to discuss some common requests, specifically home birth, water birth, placentophagy, lotus birth, vaccination refusal, and vaginal seeding, including evidence-based recommendations, perceived benefits, and potential maternal and neonatal consequences. Evidence Acquisition A literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…3 Individual variations in the microbiome are hypothesized to affect host health, and differences in the microbiota between cesarean-born and vaginal-born infants have been previously investigated. 2,4,5 The newborn infant has previously been considered sterile, and studies have demonstrated that vaginal-born infants acquire a microbiome similar to the maternal vaginal microbiome, whereas cesarean-born infants acquire a microbiome that resembles the microbial composition of maternal skin or operating room flora. 2 Therefore, vaginal seeding is a practice developed to trans-fer the maternal vaginal microbiome to cesarean-born infants to address the potential impact of an altered microbiome on the future risk of the development of immune and metabolic disorders in the infant.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Individual variations in the microbiome are hypothesized to affect host health, and differences in the microbiota between cesarean-born and vaginal-born infants have been previously investigated. 2,4,5 The newborn infant has previously been considered sterile, and studies have demonstrated that vaginal-born infants acquire a microbiome similar to the maternal vaginal microbiome, whereas cesarean-born infants acquire a microbiome that resembles the microbial composition of maternal skin or operating room flora. 2 Therefore, vaginal seeding is a practice developed to trans-fer the maternal vaginal microbiome to cesarean-born infants to address the potential impact of an altered microbiome on the future risk of the development of immune and metabolic disorders in the infant.…”
mentioning
confidence: 99%
“…Vaginal seeding is performed by incubating a gauze within the maternal vagina and subsequently inoculating the infant by swabbing the skin, mouth, nose, and/or eyelids after delivery. 2,4 Prior work in a small pilot series of seven vaginal-born, seven cesarean-born, and four cesarean-born, vaginally seeded infants demonstrated that vaginal seeding was associated with infant microbiomes that more resembled vaginal-born infants, especially in skin and anal samples for 30 days after delivery. 5 These findings have garnered interest by the public and media; however, vaginal seeding is not currently recommended outside of formal research protocols because of current data being limited by low sample size, limited follow-up time, and unknown risks or benefits in published data.…”
mentioning
confidence: 99%
See 1 more Smart Citation